Mindfulness and Parents-Adolescent Conflict during Covid-19 Pandemic - Liza Marini; Rahma Yurliani; Indri Kemala Nasution; Rahmi Putrii Rangkuti (Universitas Medan Area, 2023)
This study aims to see whether there is a relationship between mindfulness and parent-adolescent conflict during the COVID-19 pandemic. The research problem is focused on the impact of the changes that occurred during the COVID-19 Pandemic, especially during the lockdown for parents and adolescents. The impact such as the difficulty of controlling children’s behavior and the emergence of parent-adolescent conflicts, that it interferes with the ability to be mindful in the family. Mindfulness and parent-adolescent conflict are measured using a Likert scale, involved 331 adolescents aged 16-21 years (students) in Medan City. The research method used in this research is quantitative with the type of correlational research and analyzed using descriptive analysis and Pearson correlation. The results showed a negative correlation (r = -0.987), where the higher the level of Mindfulness, the lower the level of Parents-Adolescent Conflict. On the mindfulness score, 32 people (10%) are high category, 288 people (87%) are medium category, and 11 people (3%) are low category. On the parent-adolescent conflict score, 2 people (1%) are high category, 307 people (93%) are medium category, and 22 people (6%) are low category.